CASE STUDY: THE EFFECT OF HEALTHY EATING PATTERNS ON STUDENTS' LEARNING CONCENTRATION - Ayla Azzura; Teuku Bertha Firdana; Nurhannas Sura Bimanta Sitepu; Fathurrahman Simatupang (PT. Radja Intercontinental Publishing, 2025)
A healthy diet plays an important role in supporting students’ cognitive performance and concentration in learning. This article discusses the effects of proper nutrition, such as omega-3 fatty acids, iron, B-complex vitamins, and antioxidants, on brain function, memory, and focus. These nutrients help maintain energy stability, improve focus, and reduce mental fatigue and stress that often interfere with learning. Conversely, a diet rich in sugar, processed foods, and saturated fats can have a negative impact on concentration and academic performance. Students who consume nutritious foods show improved academic performance and better mental health. Therefore, maintaining a healthy diet is essential to supporting cognitive function and achieving optimal academic performance.